Knowledge brokering at the science—policy interface: designated knowledge brokers or scientists as boundary spanners in practice? - Sodomkova, Kristina (Cranfield University, 2013)
The environmental sector has witnessed a steep increase in the number of published studies promoting knowledge brokering as a solution for bridging the alleged science—policy gap. A critical review exposed knowledge brokering as an ambiguous concept of contested meaning; imputed to a prevailing conceptualization of science and policy as two distinct homogenous entities, which originated from positivism of the natural sciences paradigm. This thesis challenges the knowledge brokering concept further by showing how thirty scientists within a UK university constructed the practice of spanning a boundary between science and policy. Three discursive constructions of scientists-cum-boundary spanners emerged (Contractor, Confidant, Educator), which differed in the type of relationship between a scientist and a (policy) client and a project stage involvement. A thematic analysis revealed key influences on boundary spanning practice: access, experiential knowledge, reciprocity, trust, and repeat work. The scientists did span boundaries; the practice was strongly dependent on social relationships that were enduring and could not be reduced to the economic transaction of goods (due to the equal importance of cultural and social capital). The preferred construction was of boundary spanning as a cyclical, rather than a linear process. The research contributes to knowledge by drawing from Sociology of Scientific Knowledge and research on Higher Education, and boundary spanning. Firstly, it supports the view that science is a social practice; for its study the model of science as competition is considered most appropriate. Secondly, it adds to the understanding of scientific practice by identifying three distinct modi operandi influenced by ideologies of neoliberalism: Trust-based practices, accountable and transparent practices, and risk-taking practices. Thirdly, the study refutes the call for designated knowledge brokers as simplistic. It explores feasibility of both designated and informal boundary spanning roles within Higher Education.
Keywords: Knowledge brokering; knowledge broker; scientific practice; symbolic captial; commodification of scientific knowledge; trust